Agricultural production, relative prices, entitlements, and poverty - Srinivasan, T. N. (International Food Policy Research Institute, 1985)
Dharm Narain joined the staff of the International Food Policy Research Institute in Washington soon after Ahluwalia had completed his now-celebrated paper (Ahluwalia 1978a). In his inimitable, methodical, unhurried style Dharm Narain applied his mind to the same problem.